Kidney Transplantation and Its Impact on Quality Of Life: An Integrative Review. - Kohl Hemsing, Felipe; De Oliveira Vieira, Taiane; De Pereira, Isadora Martins; Campos, Rejane Silveira; de Oliveira Machado, Elisiane; De Godoy Mallmann, Josiane; DAvila Henrique, Jefferson (JURNAL VNUS (Vocational Nursing Sciences), 2025)
Chronic kidney disease (CKD) is highly prevalent worldwide and carries significant morbidity and mortality rates. Kidney transplantation is the last-line therapy for patients with end-stage renal disease. The quality of life after kidney transplantation is a widely studied topic, given its importance in assessing not only the clinical aspects but also the overall impact on the patient's life. This study aims to analyze the key impacts of kidney transplantation on the quality of life of transplant recipients. An integrative literature review was conducted using the Virtual Health Library (VHL) and PubMed databases. Articles were selected between April and June 2025 using the descriptors "kidney transplantation," "quality of life," and "transplant recipient," combined with the Boolean operator AND. Inclusion criteria were primary studies published in national and international journals within the last five years. Exclusion criteria were review articles, experience reports, editorials, articles requiring a subscription for open access, and studies that did not address the research question. The guiding question of this study was: What are the main impacts of kidney transplantation on the quality of life of patients after the procedure? Kidney transplantation significantly improves the quality of life and physical well-being, such as the ability to resume daily activities, enhanced self-esteem, reduced depressive symptoms, and increased autonomy. However, these benefits are accompanied by challenges, including side effects of immunosuppressive medications, sleep disorders, and physical limitations. Continuous care is essential, emphasizing the need for a multidisciplinary approach. The results highlight the positive influence of transplantation on work capacity and social reintegration, though factors like age, education level, and access to rehabilitation can affect this process. Psychologically, patients show significant improvements in mental well-being post-transplant compared to those on dialysis, with reduced levels of depression, anxiety, and stress. However, the side effects of immunosuppressants may lead to mood swings, insomnia, and fear of graft rejection. While kidney transplantation leads to significant improvements in the patients' quality of life particularly in physical, psychological, and social domains these benefits are not without challenges. Recipients face ongoing issues such as immunosuppressive side effects, sleep disturbances, functional and mental limitations, and the need for continuous multidisciplinary care